Formation of environmental consciousness of the senior preschool Age children by means of artistically- imaginative mastering of nature - Портян, М. О.; Калугіна, О. В. (Scientific notes of the pedagogical department, 2020)
The article theoretically substantiated and developed the technology of formation the ecological consciousness of children of preschool age by means of artistic and figurative mastering of nature on the basis of L. Zankov’s ideas. In the process of research, the components of the ecological consciousness of children of the senior preschool age were determined: aesthetic feeling, imaginative perception and thinking, ecological knowledge, feelings of belonging and union with nature as a universal human value. To determine the eﬀectiveness of the developed technology, the authors of the article define the criteria for the formation the ecological consciousness of children of the senior preschool age by means of artistically- imaginative mastering of nature (motivational, informative and personal) and levels of formation (high, medium, low). The motivational criterion was characterized by such an indicator as the desire and interest of the artistic and aesthetic perception of nature and art works. The informative criterion determines the level of formation ecological knowledge and thinking. The personal criterion was characterized by such an indicator as critical thinking, a subjective attitude to the natural world. For the pedagogical experiment, an experimental group EG (58 children) and a control group KG (60 children) were created. The theoretically grounded and realized technology of formation ecological consciousness of children of the senior preschool age by means of artistically-imaginative mastering of nature allowed to provide: children desire and interest in the artistic and aesthetic perception of nature and art works; perfection of artistically-imaginative perception nature world, formation of elementary ecological knowledge and thinking, which is the basis of the subjective attitude to nature. A comparative analysis of the results of the experimental and control groups allowed us to detect the growth of the criteria we set for the formation of the ecological consciousness of children of the senior preschool age by means of artistically-imaginative mastering of nature.